Expression of Alkaline Protease from Bacillus Stearothermophilus F1 in Pichia Pastoris - Ahmad Latiffi, Amaliawati (2008)
Studies have revealed that Pichia pastoris expression system is able to improve the expression level of heterologous protein. The system has successfully improved the production of foreign proteins from animal, plant and microorganism. This study was designed to produce a thermostable protease in P. pastoris expression system in order to obtain higher yields of the enzyme. The thermostable alkaline protease gene from Bacillus stearothermophilus F1 was amplified from the recombinant plasmid pTrcHis/F1 protease gene by PCR. Primer pairs were designed to amplify the F1 protease gene with and without its native signal sequence respectively. The former was designed to clone F1 protease native signal sequence by distrupting the Kex2 site of the Saccharomyces cerevisiae α-mating factor sequence. The DNA 1.23 kb and 1.16 kb fragments which contain recognition enzyme sites were cloned into expression vectors, pGAPZαB (constitutive) and pPICZαB (methanol inducible). These are shuttle vectors, therefore the recombinant constructs were transformed into Escherichia coli strain TOP 10 and DH5α respectively for propagation purposes prior to transformation into Pichia hosts. These recombinant plasmids were later introduced into P. pastoris strain SMD1168H (protease deficient strain) and GS115 respectively by electroporation. The selection of positive transformants was done on YPD agar containing 1 M of sorbitol and 100 μg/ml zeocin. The highest F1 protease yield under the control of GAP promoter was obtained after cultivation for 72 h and the maximum yield via AOX promoter obtained after 48 h induction with 0.5% methanol. Expression of F1 protease was greater in the recombinant constructs harboring the constitutive system (GE10SM, GE6GS, GX7SM, GX17GS) than in the inducible system (PE56SM, PE16GS, PX57SM, PX20GS). In both systems, the recombinant F1 protease was secreted successfully into the culture medium driven by the α-factor secretion signal and F1 gene native signal sequence. However, the expression and secretion of F1 protease utilizing the former (GE10SM, GE6GS, PE56SM, PE16GS) produced higher results relative to secretion by the native signal sequence of F1 protease (GX7SM, GX17GS, PX57SM, PX20GS). There were no large differences in yield by both P. pastoris strain SMD1168H (protease deficient strain) and GS115 host strains used. However, the best yield was obtained from clone GE6GS, which was strain GS115 harboring the recombinant gene under the control of the constitutive promoter and secretion driven by the α-factor secretion signal sequence. YTPD was found to be the best medium, producing the highest expression level (4.13 U/ml). The expression level was doubled relative to the expression by E. coli system. YTPD was modified from YTPM medium used in the expression of methanol inducible promoter. The F1 protease was constitutively expressed containing C-terminal His6-tag fusion with 34 kDa molecular weight. These data show that the expression level of F1 protease gene can be increased in P. pastoris system without affecting the enzyme function.